Produção e caracterização de compostos à base de MgB4O7 para aplicação em dosimetria - Souza, Luiza Freire de (2016)
Many materials with luminescent properties are used for ionizing radiation dosimetry through the thermoluminescence (TL) and optically stimulated luminescence (OSL) techniques. Detectors based on lithium fluoride (LiF), calcium sulphate (CaSO4) and aluminum oxide (Al2O3), doped or codoped with various elements, are the TL or OSL commercial dosimeters most widely used currently. However, several researches are focused to the development of new TL /OSL materials aiming to enhance the dosimetric properties, since no TL/OSL dosimeter has all the ideal characteristics for monitoring radiation. In this context, magnesium tetraborate (MgB4O7), which has been presented in the literature as a material for TL dosimetry, was investigated in this work. As there are no reports on the structural characterization of this material or regarding its applicability in OSL dosimetry, the proposal of the present work was to develop compounds based on MgB4O7, with different doping, by solid state synthesis. It was made the structural, optical, TL and OSL characterization of the compound to verify its feasibility for application in radiation dosimetry. Initially, it was determined the calcination temperature and time for MgB4O7 formation, with the use of thermal analyses and x ray diffraction. We produced , in powder form, the compounds:MgB4O7, MgB4O7:Dy, MgB4O7:Dy,Li, MgB4O7:Ce, MgB4O7:Ce,Li, MgB4O7:Nd and MgB4O7:Nd,Li. For TL and OSL analyses it were produced pellets sintering at 950º C for 2 hours. The radioluminescence (RL) results from the MgB4O7:Dy and MgB4O7:Dy,Li composites shows wavelength emissions at 490, 590, 670 and 760 nm. For MgB4O7:Ce and MgB4O7:Ce,Li composites, we observed a wide emission band in the ultraviolet region. With the results obtained from the TL characterization, we also discuss aspects such as: effect of sintering and dopant concentrations in emissions, influence of doping and codoping with Li in MgB4O7 matrix, thermal treatment reuse, TL signal reproducibility, dose response curve, relative sensitivity and we analyzed the kinetic parameters of the TL emission curves. The OSL analyses of MgB4O7:Dy,Li,MgB4O7:Ce,Li and MgB4O7:Nd,Li indicate that the compounds have high cross section for photoionization to the wavelength emitted by blue LEDs, and from three compounds analyzed the MgB4O7: Ce,Li showed greater sensitivity.Partial preheating and partial cleaning methods allowed to elucidate the OSL phenomenology in compounds.